Eculizumab and refractory membranoproliferative glomerulonephritis - Radhakrishnan, Seetha; Kirschfink, Michael (The New England journal of medicine, 2012)
This letter to the editor discusses the use of eculizumab in refractory membranoproliferative glomerulonephritis. The response appears to be dramatic.
Gesehen am 26.11.2018